A preparation method of surface-coated modified lithium nickel manganese oxide material
The surface-coated lithium nickel manganese oxide material addresses stability and conductivity issues by using a fluorodeoxyglucose-assisted hydrothermal method and dextran-aluminum isopropoxide coating, resulting in enhanced cycle and thermal stability with improved lithium ion storage.
Patent Information
- Application Number
- CN202411394701.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Lithium nickel manganese oxide (LNiMnO4) faces challenges in practical applications due to poor cycle stability, limited rate performance, and thermal stability issues, which limit its widespread use in high-performance lithium-ion batteries.
A surface-coated modified lithium nickel manganese oxide material is prepared using a fluorodeoxyglucose-assisted hydrothermal method to create hollow micron-spherical particles, followed by dextran encapsulation and aluminum isopropoxide coating, forming an alumina-carbon composite protective film to enhance stability and conductivity.
The modified material exhibits improved cycle stability, rate performance, and thermal stability, reducing diffusion resistance and enhancing lithium ion storage capacity, while preventing electrolyte decomposition and manganese ion dissolution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery materials, and in particular to a method for preparing a surface-coated modified lithium nickel manganese oxide material. Background Art
[0002] As the global demand for clean energy and sustainable energy storage solutions continues to grow, lithium-ion batteries have been widely used in electric vehicles, portable electronic devices and large-scale energy storage systems due to their advantages such as high energy density, long cycle life and no memory effect.
[0003] Lithium Nickel Manganese Oxide (LiNi 0.5 Mn 1.5 As a low-cost, environmentally friendly and resource-rich cathode material, lithium nickel manganese oxide (LNiMnO4) has attracted much attention due to its high theoretical capacity and good thermal stability. However, LNiMnO4 still faces some challenges in practical applications, including poor cycle stability, limited rate performance and thermal stability issues under extreme conditions. These issues limit its widespread application in high-performance lithium-ion batteries.
[0004] In order to solve the above problems, the use of aluminum oxide to coat lithium nickel manganese oxide is a common technology to improve the performance of lithium-ion battery positive electrode materials. This surface modification method aims to improve the electrochemical stability, cycle life and safety of the material by forming a protective film. However, although aluminum oxide can improve the stability of the material, it is essentially an insulating material and may increase the internal resistance of the battery, thereby affecting the conductivity and power performance of the battery.
[0005] Therefore, the applicant prepared a surface-coated modified lithium nickel manganese oxide material to solve the above problems. Summary of the invention
[0006] In order to solve the existing technical problems, the present invention discloses a method for preparing a surface-coated modified lithium nickel manganese oxide material, comprising the following preparation steps:
[0007] (1) Hollow micron-spherical lithium nickel manganese oxide materials were prepared by a fluorodeoxyglucose-assisted hydrothermal method;
[0008] (2) The hollow micron-spherical lithium nickel manganese oxide material is coated once with dextran to obtain a coated lithium nickel manganese oxide material; the dextran enters the hollow micron-spherical lithium nickel manganese oxide material through the pores of the hollow micron-spherical lithium nickel manganese oxide material and adheres to the surface of the hollow micron-spherical lithium nickel manganese oxide material, thereby improving the problem that the surface of the hollow micron-spherical lithium nickel manganese oxide material is not easy to be coated with alumina due to surface fluorination of the hollow micron-spherical lithium nickel manganese oxide material, and facilitating the subsequent adhesion of the alumina layer to the surface of the hollow micron-spherical lithium nickel manganese oxide material;
[0009] (3) using an aluminum isopropoxide solution to perform a secondary coating on the lithium nickel manganese oxide material that has been coated once, and then performing a heat treatment and sintering under an inert mixed gas to obtain a surface-coated modified lithium nickel manganese oxide material;
[0010] Furthermore, the specific steps of step (1) are as follows: nickel acetate tetrahydrate, manganese acetate tetrahydrate and urea are mixed in a molar ratio of 1:3:8, added into distilled water 30 times the mass of nickel acetate tetrahydrate and stirred for 10-20 minutes, then ethylene glycol 20 times the mass of nickel acetate tetrahydrate is measured, stirring is continued for 10-20 minutes and the temperature is controlled at 50°C, then fluorodeoxyglucose solution is added, wherein the mass of fluorodeoxyglucose is 0.8-1.2 times the mass of nickel acetate tetrahydrate, stirring is continued for 1 hour, then hydrothermal reaction is carried out at 180°C for 10 hours, and after the temperature is naturally cooled to room temperature, The mixture was centrifugally washed with distilled water for 5 to 6 times, and washed with 95% ethanol for 2 to 3 times, and then dried in an oven at 60°C for 8 to 12 hours, and then mixed with lithium carbonate (1 times the mass of nickel acetate tetrahydrate) and anhydrous ethanol (30 times the mass of nickel acetate tetrahydrate) and stirred for 20 to 40 minutes, wherein the lithium carbonate was in excess of 7% to compensate for the lithium loss at high temperature. After the ethanol was completely evaporated, the mixture was evenly ground into powder, and then sintered at 450°C for 4 hours, and then sintered at 850°C for 12 hours, and naturally cooled to room temperature to obtain a hollow micron spherical lithium nickel manganese oxide material. The heating rate of this step was 5°C / min throughout the whole process.
[0011] During the hydrothermal reaction, glucose dehydration generates oligosaccharides and aromatic compounds. Then, as the temperature continues to rise, the oligosaccharides undergo intermolecular cross-linking reactions at high temperatures to form carbon microspheres with active functional groups. At the same time, urea decomposes at high temperatures to provide CO3 2- and OH - , with Ni 2+ and Mn 2+The carbon microspheres act as the nucleation matrix for crystallization and guide the crystals to grow and aggregate on their surface to form micron-sized spheres. Finally, the carbon cores are removed through a high-temperature calcination step to form a special hollow morphology, which increases the specific surface area and pore volume of the lithium nickel manganese oxide material, reduces the diffusion resistance, and improves the rate capability of the material. At the same time, it also greatly enhances the ability to store lithium ions and improves the discharge specific capacity. The stable structure ensures the integrity of the electrode during the charge and discharge process. At the same time, the micron-sized structure can effectively reduce the occurrence of interface side reactions and reduce The capacity attenuation is reduced, thereby improving the cycle stability and rate performance of the lithium nickel manganese oxide material. At the same time, a fluorodeoxyglucose-assisted hydrothermal method is used to prepare a hollow micron-spherical lithium nickel manganese oxide material, and fluorine is introduced into the lithium nickel manganese oxide material to fluorinate the surface of the lithium nickel manganese oxide material, thereby improving the thermal stability of the lithium nickel manganese oxide material. After fluorine doping, the valence of manganese is reduced, and the lattice constant of the fluorinated lithium nickel manganese oxide material is increased, which is more conducive to the diffusion of lithium ions. Secondly, the volume change of the unit cell structure of the fluorine-doped lithium nickel manganese oxide material is smaller, which is beneficial to the stability of the lithium nickel manganese oxide material and improves the high-rate cycle performance of the lithium nickel manganese oxide material.
[0012] Aluminum isopropoxide is hydrolyzed to form alumina sol, which is better coated on the surface of the lithium nickel manganese oxide material by sticky dextran. After subsequent sintering, the dextran is carbonized to form an alumina-carbon composite protective film on the surface of the lithium nickel manganese oxide material that is once coated, thereby reducing the side reaction between the positive electrode material and the electrolyte, especially when operating under high pressure, which helps to prevent electrolyte decomposition and dissolution of manganese ions. At the same time, the carbonization of dextran forms an amorphous carbon 3D conductive network in the hollow micron-spherical lithium nickel manganese oxide material, further enhancing the cycle stability of the lithium nickel manganese oxide material and improving the problem of low conductivity of the lithium nickel manganese oxide material.
[0013] Furthermore, the concentration of the fluorodeoxyglucose solution is 45 mg / ml.
[0014] Furthermore, the specific steps of step (2) are as follows: dextran, hollow micron spherical lithium nickel manganese oxide material and ethanol are mixed in a mass ratio of 0.08-0.12:1:5 and placed in an agate ball mill for wet ball milling for 2 hours, followed by drying at 60°C for 2-4 hours to obtain a once-encapsulated lithium nickel manganese oxide material.
[0015] Furthermore, the secondary encapsulation step of step (3) is as follows: mixing the primary encapsulated lithium nickel manganese oxide material and aluminum isopropoxide solution, wherein the mass ratio of the homemade lithium nickel manganese oxide to aluminum isopropoxide is 1:0.005-0.015, followed by 30kHz ultrasonic dispersion for 25-30 minutes and then drying at 90°C for 8 hours.
[0016] Furthermore, the preparation method of the aluminum isopropoxide solution is as follows: aluminum isopropoxide and deionized water are mixed at a molar ratio of 1:5-9, and stirred at 75° C. for 5 hours to obtain the aluminum isopropoxide solution.
[0017] Furthermore, the inert mixed gas is obtained by mixing argon and hydrogen in a volume percentage of 5%:95%.
[0018] Furthermore, the heat treatment sintering temperature is 500-700°C, the sintering time is 8h, and the heating rate is 6°C / min.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] When preparing the surface-coated modified lithium nickel manganese oxide material, the present invention first adopts a fluorodeoxyglucose-assisted hydrothermal method to prepare a hollow micron-sized spherical lithium nickel manganese oxide material; then dextran is used to encapsulate the hollow micron-sized spherical lithium nickel manganese oxide material once to obtain a once-encapsulated lithium nickel manganese oxide material; then aluminum isopropoxide solution is used to encapsulate the once-encapsulated lithium nickel manganese oxide material twice; finally, heat treatment and sintering are performed under an inert mixed gas to obtain a surface-coated modified lithium nickel manganese oxide material. The obtained surface-coated modified lithium nickel manganese oxide material has good cycle stability, rate performance and thermal stability.
[0021] During the hydrothermal reaction, glucose dehydration generates oligosaccharides and aromatic compounds. Then, as the temperature continues to rise, the oligosaccharides undergo intermolecular cross-linking reactions at high temperatures to form carbon microspheres with active functional groups. At the same time, urea decomposes at high temperatures to provide CO3 2- and OH - , with Ni 2+ and Mn 2+The carbon microspheres act as the nucleation matrix for crystallization and guide the crystals to grow and aggregate on their surface to form micron-sized spheres. Finally, the carbon cores are removed through a high-temperature calcination step to form a special hollow morphology, which increases the specific surface area and pore volume of the lithium nickel manganese oxide material, reduces the diffusion resistance, and improves the rate capability of the material. At the same time, it also greatly enhances the ability to store lithium ions and improves the discharge specific capacity. The stable structure ensures the integrity of the electrode during the charge and discharge process. At the same time, the micron-sized structure can effectively reduce the occurrence of interface side reactions and reduce The capacity attenuation is reduced, thereby improving the cycle stability and rate performance of the lithium nickel manganese oxide material. At the same time, a fluorodeoxyglucose-assisted hydrothermal method is used to prepare a hollow micron-spherical lithium nickel manganese oxide material, and fluorine is introduced into the lithium nickel manganese oxide material to fluorinate the surface of the lithium nickel manganese oxide material, thereby improving the thermal stability of the lithium nickel manganese oxide material. After fluorine doping, the valence of manganese is reduced, and the lattice constant of the fluorinated lithium nickel manganese oxide material is increased, which is more conducive to the diffusion of lithium ions. Secondly, the volume change of the unit cell structure of the fluorine-doped lithium nickel manganese oxide material is smaller, which is beneficial to the stability of the lithium nickel manganese oxide material and improves the high-rate cycle performance of the lithium nickel manganese oxide material.
[0022] Aluminum isopropoxide is hydrolyzed to form alumina sol, which is better coated on the surface of the lithium nickel manganese oxide material by sticky dextran. After subsequent sintering, the dextran is carbonized to form an alumina-carbon composite protective film on the surface of the lithium nickel manganese oxide material that is once coated, thereby reducing the side reaction between the positive electrode material and the electrolyte, especially when operating under high pressure, which helps to prevent electrolyte decomposition and dissolution of manganese ions. At the same time, the carbonization of dextran forms an amorphous carbon 3D conductive network in the hollow micron-spherical lithium nickel manganese oxide material, further enhancing the cycle stability of the lithium nickel manganese oxide material and improving the problem of low conductivity of the lithium nickel manganese oxide material. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.
[0024] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows:
[0025] The dextran used is the dextran with a molecular weight of 20,000 produced by Xi'an Qiyue Biotechnology Co., Ltd. Example 1
[0026] A method for preparing a surface-coated modified lithium nickel manganese oxide material, the preparation steps are as follows:
[0027] (1) Nickel acetate tetrahydrate, manganese acetate tetrahydrate and urea were mixed in a molar ratio of 1:3:8, added to distilled water 30 times the mass of nickel acetate tetrahydrate and stirred for 10 min, then ethylene glycol 20 times the mass of nickel acetate tetrahydrate was added, stirring was continued for 10 min while controlling the temperature at 50°C, then 45 mg / ml fluorodeoxyglucose solution was added (the mass of fluorodeoxyglucose was 0.8 times the mass of nickel acetate tetrahydrate), stirring was continued for 1 h, then hydrothermal reaction was carried out at 180°C for 10 h, and after the temperature was naturally cooled to room temperature, the mixture was deionized with distilled water. The mixture was washed 5 times with the core and washed twice with 95% ethanol, then dried in an oven at 60°C for 8 hours, then mixed with lithium carbonate (1 times the mass of nickel acetate tetrahydrate) and anhydrous ethanol (30 times the mass of nickel acetate tetrahydrate) and stirred for 20 minutes, wherein the lithium carbonate was in excess of 7% to compensate for the loss of lithium at high temperature, and after the ethanol was completely evaporated, it was evenly ground into powder, then sintered at 450°C for 4 hours, sintered at 850°C for 12 hours, and naturally cooled to room temperature to obtain a hollow micron spherical nickel manganese oxide material; the heating rate of this step was 5°C / min throughout the whole process;
[0028] (2) Mixing dextran, hollow micron-shaped spherical lithium nickel manganese oxide material and ethanol in a mass ratio of 0.08:1:5, placing them in an agate ball mill, and wet-milling them for 2 hours, followed by drying at 60° C. for 2 hours to obtain a primary-coated lithium nickel manganese oxide material;
[0029] (3) The once coated lithium nickel manganese oxide material and aluminum isopropoxide solution were mixed, wherein the mass ratio of the homemade lithium nickel manganese oxide to aluminum isopropoxide was 1:0.005, followed by 30 kHz ultrasonic dispersion for 25 min and then drying at 90 °C for 8 h. Then, the temperature was increased to 500 °C at 6 °C / min in a hydrogen atmosphere doped with 5% argon and kept at this temperature for 8 h to obtain a surface-coated modified lithium nickel manganese oxide material. Example 2
[0030] A method for preparing a surface-coated modified lithium nickel manganese oxide material, the preparation steps are as follows:
[0031] (1) Nickel acetate tetrahydrate, manganese acetate tetrahydrate, and urea were mixed in a molar ratio of 1:3:8, added to distilled water 30 times the mass of nickel acetate tetrahydrate, and stirred for 15 minutes. Then, ethylene glycol 20 times the mass of nickel acetate tetrahydrate was measured, and the stirring was continued for 15 minutes while controlling the temperature at 50°C. Then, 45 mg / ml of fluorodeoxyglucose solution was added, where the mass of fluorodeoxyglucose was 1 times that of nickel acetate tetrahydrate. The stirring was continued for 1 hour, and then hydrothermal reaction was carried out at 180°C for 10 hours. After the temperature was naturally cooled to room temperature, the mixture was centrifuged with distilled water. Wash 6 times, and wash 3 times with 95% ethanol, then bake in an oven at 60°C for 10 hours, then mix and stir with 1 times the amount of nickel acetate tetrahydrate with lithium carbonate and 30 times the mass of nickel acetate tetrahydrate with anhydrous ethanol for 30 minutes, wherein the lithium carbonate is 7% in excess to compensate for the loss of lithium at high temperature, and grind evenly into powder after the ethanol is completely evaporated, then sinter at 450°C for 4 hours, sinter at 850°C for 12 hours, and naturally cool to room temperature to obtain a hollow micron spherical nickel manganese oxide material; the heating rate of this step is 5°C / min throughout the whole process;
[0032] (2) Mixing dextran, hollow micron spherical lithium nickel manganese oxide material and ethanol in a mass ratio of 0.1:1:5, placing them in an agate ball mill, and wet-milling them for 2 hours, followed by drying at 60°C for 3 hours to obtain a primary-coated lithium nickel manganese oxide material;
[0033] (3) The once coated lithium nickel manganese oxide material and aluminum isopropoxide solution were mixed, wherein the mass ratio of the homemade lithium nickel manganese oxide and aluminum isopropoxide was 1:0.01, followed by 30 kHz ultrasonic dispersion for 30 min and then drying at 90 °C for 8 h. Then, the temperature was increased to 700 °C at 6 °C / min in a hydrogen atmosphere doped with 5% argon and kept at this temperature for 8 h to obtain a surface-coated modified lithium nickel manganese oxide material. Example 3
[0034] A method for preparing a surface-coated modified lithium nickel manganese oxide material, the preparation steps are as follows:
[0035] (1) Nickel acetate tetrahydrate, manganese acetate tetrahydrate and urea were mixed in a molar ratio of 1:3:8, added to distilled water 30 times the mass of nickel acetate tetrahydrate and stirred for 20 min, then ethylene glycol 20 times the mass of nickel acetate tetrahydrate was added, stirring was continued for 20 min while controlling the temperature at 50°C, then 45 mg / ml fluorodeoxyglucose solution was added (the mass of fluorodeoxyglucose was 1.2 times that of nickel acetate tetrahydrate), stirring was continued for 1 h, then hydrothermal reaction was carried out at 180°C for 10 h, and after the temperature was naturally cooled to room temperature, the mixture was deionized with distilled water. The mixture was washed 6 times with the core, and washed 3 times with 95% ethanol, and then dried in an oven at 60°C for 12 hours, and then mixed with lithium carbonate (1 times the mass of nickel acetate tetrahydrate) and anhydrous ethanol (30 times the mass of nickel acetate tetrahydrate) and stirred for 40 minutes, wherein the lithium carbonate was in excess of 7% to compensate for the lithium loss at high temperature, and after the ethanol was completely evaporated, it was evenly ground into powder, and then sintered at 450°C for 4 hours, and then sintered at 850°C for 12 hours, and naturally cooled to room temperature to obtain a hollow micron spherical nickel manganese oxide material; the heating rate of this step was 5°C / min throughout the whole process;
[0036] (2) Mixing dextran, hollow micron-shaped spherical lithium nickel manganese oxide material and ethanol in a mass ratio of 0.12:1:5, placing them in an agate ball mill, and wet-milling them for 2 hours, followed by drying at 60° C. for 4 hours to obtain a primary-coated lithium nickel manganese oxide material;
[0037] (3) The once coated lithium nickel manganese oxide material and aluminum isopropoxide solution were mixed, wherein the mass ratio of the homemade lithium nickel manganese oxide to aluminum isopropoxide was 1:0.015, followed by 30 kHz ultrasonic dispersion for 30 min and then drying at 90 °C for 8 h. Then, the temperature was increased to 600 °C at 6 °C / min in a hydrogen atmosphere doped with 5% argon and kept at this temperature for 8 h to obtain a surface-coated modified lithium nickel manganese oxide material.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 and Example 2 is that the hollow micron-spherical lithium nickel manganese oxide material is prepared by a glucose-assisted hydrothermal method, and the remaining steps and components are the same as those in Example 2.
[0040] Comparative Example 2
[0041] The difference between Comparative Example 2 and Example 2 is that the nickel manganese oxide NiLi produced by Chengdu Xingneng New Materials Co., Ltd. is used. 0.5 Mn 1.5 O4 was packaged once and twice in sequence, and the remaining steps and ingredients were the same as in Example 2.
[0042] Comparative Example 3
[0043] The difference between Comparative Example 3 and Example 2 is that only dextran is used to wrap the hollow micron-shaped spherical lithium nickel manganese oxide material, and the remaining steps and components are the same as those in Example 2.
[0044] Comparative Example 4
[0045] The difference between Comparative Example 4 and Example 2 is that only aluminum isopropoxide solution is used to wrap the hollow micron-shaped spherical lithium nickel manganese oxide material, and the remaining steps and components are the same as those in Example 2.
[0046] Effect example
[0047] The surface-coated modified lithium nickel manganese oxide material prepared in the embodiment and the comparative example was sieved, and a conductive agent SuperP and a binder PVDF (mass ratio of positive electrode material: conductive agent: binder = 8:1:1) were added, and ground with a mortar in a dry room with low humidity until the powder was fine and uniform, and then N-methylpyrrolidone (NMP) was added dropwise and continued to grind for about 20 minutes, and the homogenate was kept in a bright state. If the surface of the slurry showed a granular feel, the homogenate failed, and the grinding was re-weighed; after grinding, it was coated on the surface of aluminum foil, and a coating film was pulled out with an SZQ preparation device, with a thickness of 150 μm, and transferred to a drying oven at 60°C for 12 hours, and then taken out and cut into a circular positive electrode sheet with a diameter of 14 mm with a sheet cutter, and placed in a vacuum drying oven at 120°C again, and dried for 12 hours, taken out and accurately weighed for use;
[0048] The entire button battery assembly process is completed in a MikrounaSuper (1220|750) argon atmosphere glove box, where the water and oxygen content is <1ppm; the battery shell model is CR2032, the diaphragm is the 2300 diaphragm produced by Celgard, cut into a diameter of 16mm, the lithium sheet purchased is the lithium sheet with a diameter of 14.5mm produced by Zhongneng Lithium Industry, and the electrolyte is a solution of 1molL-1LiPF6EC-EMC-DMC (volume ratio 1:1:1);
[0049] The detailed assembly process is as follows: first, place the negative electrode shell steadily, take out the lithium sheet with clean and dry tweezers, place it in the negative electrode shell, then use a dropper to absorb a small amount of electrolyte and add two drops on the surface of the lithium sheet, then cover the diaphragm on the surface of the lithium sheet, and use a dropper to add electrolyte to the surface of the diaphragm again, in order to completely soak both sides of the diaphragm; then place the positive electrode sheet, with the side coated with the active material (a mixture of positive electrode powder and adhesive PVDF and conductive agent SuperP) facing the electrolyte, then place the gasket and shrapnel (the convex surface of the shrapnel faces the positive electrode shell), finally use insulating tweezers to take the positive electrode shell cover on top of the shrapnel, press it tightly, and finally use a manual sealing machine to seal the battery; the assembled battery is sealed and left to stand at room temperature for 24 hours, and a series of electrochemical tests are carried out.
[0050] Table 1
[0051]
[0052] It can be found from Table 1 that the surface-coated modified lithium nickel manganese oxide material prepared in the embodiment has good cycle stability, rate performance and thermal stability; compared with Example 1, Example 2 found that the hollow micron-spherical lithium nickel manganese oxide material was prepared by a fluorodeoxyglucose-assisted hydrothermal method, and the surface-coated modified lithium nickel manganese oxide material had good cycle stability, rate performance and thermal stability; compared with Comparative Examples 2, 3 and 4, Example 2 found that the hollow micron-spherical lithium nickel manganese oxide material was wrapped twice with dextran and aluminum isopropoxide solution in turn, and the surface-coated modified lithium nickel manganese oxide material had good cycle stability and rate performance.
[0053] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A method for preparing a surface-coated modified lithium nickel manganese oxide material, characterized in that: The method comprises the following preparation steps: Step (1) adopts a fluorodeoxyglucose-assisted hydrothermal method to prepare a hollow micron spherical lithium nickel manganese oxide material; the specific steps are: nickel acetate tetrahydrate, manganese acetate tetrahydrate, and urea are mixed in a molar ratio of 1:3:8, added into distilled water 30 times the mass of nickel acetate tetrahydrate, and stirred for 10 to 20 minutes, then ethylene glycol 20 times the mass of nickel acetate tetrahydrate is measured, and the stirring is continued for 10 to 20 minutes while controlling the temperature at 50°C, and then fluorodeoxyglucose solution is added, wherein the mass of fluorodeoxyglucose is 0.8 to 1.2 times that of nickel acetate tetrahydrate, and the stirring is continued for 1 hour, and then the hydrothermal reaction is carried out at 180°C for 10 hours, and the temperature is kept at 50°C. After cooling naturally to room temperature, wash with distilled water by centrifugation for 5-6 times, and wash with 95% ethanol for 2-3 times, then bake in an oven at 60°C for 8-12 hours, then mix and stir with lithium carbonate (1 times the mass of nickel acetate tetrahydrate) and anhydrous ethanol (30 times the mass of nickel acetate tetrahydrate) for 20-40 minutes, wherein the lithium carbonate is in excess of 7% to compensate for the lithium loss at high temperature, and grind evenly into powder after the ethanol is completely evaporated, then sinter at 450°C for 4 hours, sinter at 850°C for 12 hours, and cool naturally to room temperature to obtain a hollow micron spherical nickel manganese oxide material; the heating rate of this step is 5°C / min throughout the whole process; Step (2) using dextran to encapsulate the hollow micron spherical lithium nickel manganese oxide material once to obtain a once-encapsulated lithium nickel manganese oxide material; the specific steps are as follows: dextran, hollow micron spherical lithium nickel manganese oxide material, and ethanol are mixed in a mass ratio of 0.08-0.12:1:5 and placed in an agate ball mill for wet ball milling for 2 hours, followed by drying at 60° C. for 2-4 hours to obtain a once-encapsulated lithium nickel manganese oxide material; Step (3) uses an aluminum isopropoxide solution to perform a secondary coating on the lithium nickel manganese oxide material that has been coated once, and then performs heat treatment and sintering under an inert mixed gas to obtain a surface-coated modified lithium nickel manganese oxide material; the specific steps of the secondary coating are as follows: mixing the lithium nickel manganese oxide material that has been coated once with an aluminum isopropoxide solution, wherein the mass ratio of the self-made lithium nickel manganese oxide to the aluminum isopropoxide is 1:0.005-0.015, and then performing 30kHz ultrasonic dispersion for 25-30 minutes and then drying at 90°C for 8 hours.
2. The method for preparing the surface-coated modified lithium nickel manganese oxide material according to claim 1, characterized in that: The concentration of the fluorodeoxyglucose solution is 45 mg / ml.
3. The method for preparing the surface-coated modified lithium nickel manganese oxide material according to claim 1, characterized in that: The preparation method of the aluminum isopropoxide solution is as follows: aluminum isopropoxide and deionized water are mixed at a molar ratio of 1:5-9, and stirred at 75° C. for 5 hours to obtain the aluminum isopropoxide solution.
4. The method for preparing the surface-coated modified lithium nickel manganese oxide material according to claim 1, characterized in that: The inert mixed gas is obtained by mixing argon and hydrogen in a volume percentage of 5%:95%.
5. The method for preparing the surface-coated modified lithium nickel manganese oxide material according to claim 1, characterized in that: The heat treatment sintering temperature is 500-700°C, the sintering time is 8h, and the heating rate is 6°C / min.
Citation Information
Patent Citations
Preparation method of nickel ferrite-coated lithium nickel manganese oxide positive electrode material
CN105932247A
Aluminum fluoride / silver double-coated lithium nickel cobalt manganese oxide positive electrode material and preparation method thereof
CN107591532A
